DEVELOPMENT OF INFOGRAPHIC-BASED LEARNING MEDIA ON COLONIALISM AND INDONESIAN RESISTANCE TO INCREASE LEARNING INTEREST IN CLASS XI OF SMAN 1 TAMBANG: Pengembangan Media Pembelajaran Berbasis Infografis Materi Kolonialisme Dan Perlawanan Bangsa Indonesia Untuk Meningkatkan Minat Belajar Kelas XI SMAN 1 Tambang - Alpinul fajri; AHMAL; YANUAR AL FIQRI (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The purpose of this study was to determine the feasibility and effectiveness of infographic media as a history learning medium with the material of colonialism in Indonesia. The research method used was Research and Development (RnD). Before the trial, the media was first validated by material experts with a percentage of 81% in the category of